2004
DOI: 10.1152/ajpheart.00193.2004
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin induces vasoconstriction in the rat coronary vasculature without altering cardiac peptide secretion

Abstract: We administered ghrelin, a novel growth hormone-releasing hormone, to isolated perfused rat hearts, coronary arterioles, and cultured neonatal cardiomyocytes to determine its effects on coronary vascular tone, contractility, and natriuretic peptide secretion and gene expression. We also determined cardiac levels of ghrelin and whether the heart is a source of the circulating peptide. Ghrelin dose dependently increased coronary perfusion pressure (44 +/- 9%, P < 0.01), constricted isolated coronary arterioles (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 42 publications
1
39
1
Order By: Relevance
“…Ghrelin unexpectedly increased coronary perfusion pressure and constricted isolated coronary arterioles in rats (Pemberton et al, 2004), whereas intracoronary acyl ghrelin infusion unexpectedly decreased coronary blood flow in anesthetized pigs (Grossini et al, 2007). The mechanisms were shown to involve L-type Ca 2ϩ channel and protein kinase C activation (Pemberton et al, 2004) and the inhibition of a tonic coronary ␤ 2 -adrenergic receptor-mediated vasodilatory effect related to the release of nitric oxide (Grossini et al, 2007).…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…Ghrelin unexpectedly increased coronary perfusion pressure and constricted isolated coronary arterioles in rats (Pemberton et al, 2004), whereas intracoronary acyl ghrelin infusion unexpectedly decreased coronary blood flow in anesthetized pigs (Grossini et al, 2007). The mechanisms were shown to involve L-type Ca 2ϩ channel and protein kinase C activation (Pemberton et al, 2004) and the inhibition of a tonic coronary ␤ 2 -adrenergic receptor-mediated vasodilatory effect related to the release of nitric oxide (Grossini et al, 2007).…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…Indeed, intravenous administration of ghrelin in humans causes a significant decrease in mean arterial pressure, but does not change heart rate [106]. By contrast, ghrelin increases coronary perfusion pressure in rat hearts perfused using the Langendorf system and significantly increases pressure-induced myogenic tone in coronary arterioles [117]. In the microcirculation, ghrelin increases vascular flow, and this action may affect other physiological functions of ghrelin [145].…”
Section: Cardiovascular Functionmentioning
confidence: 99%
“…In vitro a study, ghrelin has shown to prevent against the cardiotoxicity of adriamycin may be attributed to up regulation of TNF-α/NF-κB pathways, as well as its mitochondrial stabilization properties [16]. A study reported that, in anesthetized pigs, intracoronary infusion of ghrelin induced coronary artery contraction, thereby reducing coronary circulation and the mechanism of this response has been shown to involve the  To determine if anti-inflammatory mechanisms are involved we planned to measure tissue levels of the known pro-inflammatory mediators (MCP-1, IL-1β, IL-6, and VCAM-1).…”
Section: Introductionmentioning
confidence: 99%